(untitled) (Research, Society and Development, 2022)
Social relationships are of great importance in mental health as they influence the design of this care. The value of human relationships from the perspectives of what is health and what is disease is historically proven from civilizations. Professional behaviors can influence therapeutic relationships and can be a major hindrance to the promotion of mental health. Based on the ethical bias, it is necessary to highlight the professional-user relationship through embracement for the construction of the therapeutic relationship. Objective: This study aimed to analyze, through the exercise of film language, the ethical principles in the therapeutic relationship between health professionals and people in mental suffering. Methodology: Qualitative, exploratory research using the film analysis strategy. Information obtained from non-participant and indirect observation of the films: Avengers: Age of Ultron, Doctor Strange, Batman vs Superman: The Origin of Justice, Joker, Glass and; the miniseries: WandaVision. Results: From the analysis of the material, the information was organized into categories: The professional recognizing limits and limitations; Understand the dimensions of the user; Leverage user resources; Deal with and respect user limitations; Power relations. Conclusion: Based on plots based on stories of super heroes, the importance and, at the same time, the complexity of the mental health care process can be observed; and the ethical aspects that result in the promotion of mental health and depend on the behavior of professionals who work in psychosocial care.